Presente y futuro de la Unión General de Trabajadores : (1888-1925) / Francisco Largo Caballero; [presentación de Cándido Méndez] - Méndez, Cándido (1952-); Largo Caballero, Francisco (1869-1946)
Repr. fac. de la ed. de: Madrid: Javier Morata Pedreǫ, 1925